Pro Android 2 - Hashimi, Sayed Y. (Apress : Distributed to the Book trade worldwide by Springer-Verlag, 2010)
Android, Google's open-source platform for mobile development, has the momentum to become the leading mobile platform. Pro Android 2 shows you how to build real-world mobile apps using Google's Android SDK. Android is easy to learn yet comprehensive, and is rich in functionality.--[back cover].